Capital intelectual y su incidencia en las competencias laborales de las secretarias en la Cooperativa de Ahorro y Crédito San Antonio del cantón Vinces - Solórzano Gonzáles, Sacha Margarita (2020)
The present case study, consists of the description and analysis of the topic: `` Intellectual Capital and its impact on the Labor Competencies of the secretaries in the San Antonio from Vinces town, Savings and Credit Cooperative '', aims to establish solutions that allows you to improve the situation that the cooperative is going through, for the development of this analysis the deductive method was used, obtaining information from various sources in specialized data bases, through the application of surveys to its secretaries, we proceeded to collect and analyze the information received Despite the diversity of models and approaches on intellectual capital and labor competencies, there is a widely accepted set of indicators, which can be used by its management for identification and measurement as an instrument to improve the management of its intangible assets On the other hand, in the current knowledge society, intangibles have obtained the greatest responsibility in the creation of business value, for this reason, it is very interesting to study their variables by giving them the design and identification through the analysis of various traditional approaches.